Conversioni religiose in Calderón de la Barca: ‘El gran príncipe de Fez’ (1669) - Colombo, Emanuele (Drammaturgia, 2020)
El gran príncipe de Fez (1669), one of the less studied works by the great playwright Calderón de la Barca, deals with the theme of religious conversions in the Early Modern Mediterranean through the story of Muhammad el-Attaz, prince of Fez, who converted to Christianity and entered the Society of Jesus. The play, whose genesis, fortune and sources are thoroughly examined, discloses Calderón’s vision of the exchanges between the Christian and Muslim Worlds in the Mediterranean. Moreover, some passages clearly show the playwright’s connections with the Society of Jesus, which allow him to interpret the complex phenomenon of conversions with a profoundly religious sensibility, placing it in the political context of the Seventeenth-Century Spain.